Experimental investigations on cylindrical critical flow Venturi nozzles with roughness. (October 2021) - Lambert, Marc Antoine; Maury, Rémy; Lehnasch, Guillaume; Foucault, Eric; Valière, Jean-Christophe
Abstract: In an attempt to redefine and improve the ISO9300 norm, it is possible to see the emergence of a universal ( C d ) curve. For this, all the influential factors must be correctly understood within their range of variation. In recent discussions, the experimental calibration point could be limited, and a low-pressure measurement could be sufficient to extrapolate the higher part of the curve with a relatively good level of confidence. For that purpose, the cylindrical shape gives more variations and needs a higher level of measurement to understand the behavior of the curve. Roughness level is a key parameter to this understanding. Experiments have been carried out to determine the impact of cylindrical nozzle throat roughness on C d and to demonstrate the need for precise dimensional parameters, such as diameter and roughness characterization. The results show that an increase in roughness may lead to a significant decrease in C d, particularly at high Reynolds numbers ( R e d ). A theorization is introduced based on Colebrook & White's formulation which allows the thickness boundary layer to be quantified. This study highlights the need for further investigation into both cylindrical nozzles and roughness effects on the discharge coefficient in order to improve the norm. Highlights: The evolution of the discharge coefficient Cd obtained with cylindrical CFVNs is accurately quantified in a full range of Reynolds numbers. The decrease of the discharge coefficient is a function of the increase of the nozzle wall roughness. At high Reynolds numbers, the discharge coefficient shows an asymptotic trend towards a rather constant value as a function of the roughness level. Previous models proposed to describe the evolution of the discharge coefficient for smooth nozzles are adapted to account for wall roughness.